2006
DOI: 10.1029/2006jd007193
|View full text |Cite
|
Sign up to set email alerts
|

Nighttime ozone profiles in the stratosphere and mesosphere by the Global Ozone Monitoring by Occultation of Stars on Envisat

Abstract: [1] The Global Ozone Monitoring by Occultation of Stars (GOMOS) instrument on board the European Space Agency's Envisat satellite measures ozone and a few other trace gases using the stellar occultation method. Global coverage, good vertical resolution and the self-calibrating measurement method make GOMOS observations a promising data set for building various climatologies. In this paper we present the nighttime stratospheric ozone distribution measured by GOMOS in 2003. We show monthly latitudinal distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
90
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(90 citation statements)
references
References 47 publications
0
90
0
Order By: Relevance
“…All these data permitted to validate the GOMOS previous operational processor v4.02 ozone profiles and evaluate biases for different conditions. The star temperature and magnitude determine the signal strength of the observed UV spectrum (Kyrölä et al, 2006). The magnitude defines the brightness of the star while the temperature is associated with the shape of the spectrum.…”
Section: Methodsmentioning
confidence: 99%
“…All these data permitted to validate the GOMOS previous operational processor v4.02 ozone profiles and evaluate biases for different conditions. The star temperature and magnitude determine the signal strength of the observed UV spectrum (Kyrölä et al, 2006). The magnitude defines the brightness of the star while the temperature is associated with the shape of the spectrum.…”
Section: Methodsmentioning
confidence: 99%
“…Lossow et al (2008), using sub-mm radiometer (SMR) data from the Odin spacecraft (Murtagh et al, 2002), observed the MSAO in H 2 O mixing ratio, the maxima at 90 km occurring in the solstice periods. Kyrölä et al (2006Kyrölä et al ( , 2010, using Envisat/GOMOS (Global Ozone Monitoring by Occultation of Stars) data, found that ozone (O 3 ) at 90 km peaked in equinox periods and was approximately a factor of three lower in solstice periods. Huang et al (2008) and Smith et al (2008) found a similar variation in O 3 using data from TIMED/SABER (Sounding of the Atmosphere using Broadband Emission Radiometry).…”
Section: R L Gattinger Et Al: the Roles Of Vertical Advection And mentioning
confidence: 99%
“…For the seasonal variation of the O 3 profiles in the upper mesosphere the chosen reference measurements are the nighttime observations of Kyrölä et al (2006Kyrölä et al ( , 2010 made with the GOMOS instrument on Envisat. Their O 3 profiles, based on a direct measurements of stellar occultation, extended to an upper altitude of approximately 100 km.…”
Section: Msao Data Driving the Model Simulationmentioning
confidence: 99%
“…A negative bias of −5% is found for GOMOS at h=45 km, while the MIPAS ozone profiles (ESA operational retrieval version IPF 4.61 and 4.62) have a positive bias of around 5% at h=20 km and h=35-45 km relative to the lidar profiles. Kyrölä et al (2006) show that GOMOS provides a higher precision at upper altitudes if only the bright star occultations are selected.…”
mentioning
confidence: 99%